Pengembangan Karakter Religius melalui Kurikuler di SD Istiqomah Kota Bandung - Mubarok, Husni; Khofifah, Nur; Khalimatusa’adah, Khalimatusa’adah; Dwiyanto, Wahyu; Kamila, Mellia (Lembaga Yasin AlSys, 2022)
This study aims to determine how the development of students’ religious character through curricular activities at SD Istiqomah Bandung. Instillling religious values is important in a school institution for the development of the caracter of student, an institution is required to be able to create a religious atmosphere trough programs or activities carried out by all school members, one of which is curricular activities, where these activities can produce, one of which is curricular activities, where these activities can produce the formation of a unity, namely religious culture in schools. This religious culture will later become religious values and underlie the behavior, daily habits, traditions, and symbols practiced by the school community. The purpose of this study was to obtain information about the development of religious character through curricular activities at SD Istiqomah Bandung. In this study, we used qualitative research through collection methods in the form of observation, interviews an documentation. Based on the results of this study proves that the development of rwligious character activities at SD Istiqomah Bandung can be implemented and developed well.